Boardwalk empire die komplette erste Staffel - Scorsese, Martin 1942-; Wahlberg, Mark 1971-; Buscemi, Steve 1957-; Pitt, Michael 1981-; Macdonald, Kelly (Home Box Office, 2011)
A lavish period drama set in Atlantic City, following the life and times of Nucky Thompson, the undisputed political and criminal mastermind whose grip on power and control of the city's liquor supply is under constant threat
Bildformat 1.78:1 (16:9) geeignet für alle Bildschirmformate
Orig.: USA 2010
Enth. Making-of "Boardwalk empire" ; Wie der Boardwalk entstand ; Figuren Profile ; Atlantic City: die Stadt der Sünde ; Speakeasy Tour ; Audiokommentare